Efficacy and safety of oral nalbuphine extended release in prurigo nodularis: results of a phase 2 randomized controlled trial with an open‐label extension phase - Weisshaar, E.; Szepietowski, J.C.; Bernhard, J.D.; Hait, H.; Legat, F.J.; Nattkemper, L.; Reich, A.; Sadoghi, B.; Sciascia, T.R.; Zeidler, C.; Yosipovitch, G.; Ständer, S. (Journal of the European Academy of Dermatology and Venereology, 2022)
Background Treatment of prurigo nodularis (PN) is challenging and new treatment options are needed. Objective To evaluate the efficacy and safety of two oral doses of the kappa opioid agonist and mu opioid antagonist nalbuphine extended release (NAL‐ER) tablets in a phase 2, multicentre, randomized, double‐blind, placebo‐controlled trial with an open‐label, 50‐week extension phase. Methods Subjects with moderate‐to‐severe PN were randomized to NAL‐ER 81 mg (NAL‐ER81) or 162 mg (NAL‐ER162) tablets twice‐daily or placebo for 8 weeks of stable dosing following a 2‐week titration period. Subjects completing Week 10 with a Worst Itch Numerical Rating Scale (WI‐NRS) score ≥5 at the time of rollover (or during the observation period) were eligible for open‐label treatment. Results Of 63 randomized subjects, 62 were treated and comprised the modified intent‐to‐treat population (MITT), 50 completed 10 weeks of treatment. In the MITT analysis, 8 subjects (44.4%) treated with NAL‐ER162 (P = 0.32) and 6 (27.3%) treated with NAL‐ER81 (P = 0.78) achieved ≥30% reduction from baseline in 7‐day WI‐NRS at Week 10 (primary efficacy endpoint) vs. 8 (36.4%) in the placebo group. Itch reduction was significant among 8/12 (66.7%) subjects completing Week 10 treated with NAL‐ER162 vs. placebo (8/20, 40.0%; P = 0.03). Additionally, 6 subjects (33.3%) treated with NAL‐ER162 and 3 (13.6%) treated with NAL‐ER81 achieved ≥50% reduction from baseline in 7‐day WI‐NRS at Week 10 (coprimary endpoint). Extended open‐label treatment was associated with further improvements in itch reduction and favourable changes in PN lesion activity as assessed by Prurigo Activity Score. Adverse events occurred predominantly during dose titration and were of mild‐to‐moderate severity. The safety profile did not change with extended open‐label treatment. Conclusion In adult subjects with PN, oral treatment with NAL‐ER 162 mg twice daily provided measurable anti‐pruritic efficacy in subjects completing ≥10 weeks of treatment and was well tolerated (ClinicalTrials.gov: NCT02174419).